Views from the other side: Party perceptions on news media in Swedish election campaigns 2010–2022 - Bolin, Niklas; Nord, Lars (Journalistica, 2024)
The study explores the perspectives of political parties regarding news media coverage in election campaigns. By analyzing official post-election analyses produced by Swedish political parties from 2010 to 2022, the study offers a novel approach to the study of political party views of news media. The findings largely support the arguments proposed by mediatization literature, highlighting the significance of media in party communication. Parties display eagerness to attract positive media attention while expressing regret over inadequate or negative publicity. More surprisingly, there is a lack of references to media bias in the reports, suggesting that the hostile media effect is not a major concern among Swedish parties. Despite criticisms related to irrelevant reporting and perceived negative coverage, party perceptions towards the media remains predominantly neutral. The study contributes to the understanding of the complex relationship between political parties and news media in the context of election campaigns.